Fiber Laser Welding of Dual-Phase and Bake-Hardened Steels - Švec, P.; Schrek, A.; Csicsó, T. (Проблемы прочности, 2016)
Microstructural changes and microhardness profiles of laser-welded dual-phase DP600 and bakehardened 220BH steels were evaluated. The joints of these steels were butted with different welding parameters. They exhibited the microstructural changes, from ferrite and martensite in dual-phase steels or ferrite in bake-hardened steels to acicular ferrite, bainite and martensite in the fusion and heat-affected zones of the weld joints. As a result of welding, microhardness increases significantly in the fusion zones and even more in the heat-affected zones near DP600 steel.